Synthesis and characterization of ferrocenylchalcogenopropargyl complexes [Fe(eta(5)-(C5H4ECH2C)-C-I CH)(2)] (E-I = Se, S) and their reactions to form unusual ferrocenyl-containing metal clusters with eclipsed Cp rings and new five-membered (FeECH)-C-I = - Mathur, P.; Singh, V. K.; Mobin, Shaikh M.; Srinivasu, C.; Trivedi, R.; Bhunia, A. K.; Puranik, Vedavati G. (Organometallics, 2005)
{The new bis(chalcogenopropargyl)ferrocene complexes [Fe(eta(5)-C(5)H(4)E(I)CH(2)CdropCH)(2)] (E-I = Se, 1; E-I = S, 2) have been prepared by treatment of the dilithiated [Fe(eta(5)-C5H4Li)(2)] with Se or S powder, followed by reaction with propargyl bromide. Reaction of 1 and 2 with [Fe2M(mu(3)-E)(2)(CO)(9)] (E = S, Se and M = Fe, Ru) forms new clusters which feature an unusual five-membered (FeECH)-C-I=CCH2 ring with a pi bond between the olefinic unit and the Fe atom, and the Cp rings adopt an eclipsed arrangement. The structures of 1 and [Fe(eta(5)-C5H4E(I)-CH(2)CdropCH) (eta(5)-C5H4{Fe2M(CO)(8)(mu-E)((ECHCCH2)-C-I)})] (M = Fe

Azadirachtin a interacts with er alpha domain and regulates bone formation - Kushwaha, P.; Khedgikar, V.; Gautam, J.; Kumar, A.; Thulasiram, Hirekodathakallu V.; Mishra, P. R.; Trivedi, P. K.; Trivedi, R. (Osteoporosis International, 2016)